Indoor Tracking for drone - Sérgio Emanuel Costa Vinha (2019)
This work addresses the tracking of autonomous drones in complex environments. The indoor tracking solution to manifest a simple cargo transport within warehouses has its drawbacks. The present work suggests some improvements to this technology. Since autonomous drones are recent in robotics, there are still work to progress. To adapt these type of flying robots to automation is a difficult task, since indoor tracking is still in big development. The problem consists in providing indoor tracking for mini-drone in warehouse environment. For this a solution based in a drone construction parallel to ultra wide-band beacons is implemented.